Detection of insect-specific viruses in mosquitoes at the Colorado State University Center for Vector-Borne and Infectious Diseases Insectary - Domenico, Lila, author; Ebel, Gregory, advisor; Geiss, Brian, committee member; Williams, Kaitlynn, committee member (Colorado State University. Libraries, 2025)
Insect-specific viruses (ISVs) are viruses that can infect arthropod cells, like ticks and mosquitoes, but not vertebrate cells. It has also been shown that ISV infections decrease the growth of arboviruses, like West Nile virus and Dengue, during experiments where mosquitoes or mosquito cell lines were coinfected. Because of this unique ability to decrease arboviral growth, combined with their inability to replicate in vertebrate cells, research has started to expand on potential biocontrol applications of ISVs. However, since arbovirus research is conducted at facilities like the insectary at the Center for Vector-Borne and Infectious Diseases (CVID), the presence of ISVs in the mosquitoes used for these studies could influence experimental outcomes. For that reason, we determined which ISVs are the most commonly found in various mosquito populations and used RT-PCR to screen multiple colonies of mosquitoes reared in the insectary at CVID. We screened for the following ISVs: Culex flavivirus, Aedes flavivirus, Cell fusing agent virus, Phasi Charoen-like virus, Kamiti River Virus, Eilat Virus, and Calbertado virus. We collected mosquitoes from different colonies of Aedes triseriatus, Aedes aegypti, Aedes albopictus, Culex quinquefasciatus, and Culex tarsalis from the insectary to screen for these ISVs. With pooled mosquito homogenates from each of these species, we extracted RNA and analyzed the extractions using RT-PCR, using previously published primers for the ISVs of interest. Our results show that, of the colonies tested from the insectary at CVID, none of the ISVs screened for were present. These findings indicate that the colonies maintained at CVID are favorable control organisms for future arboviral research.
Keywords: insect specific viruses; arboviruses; biocontrol applications